“日丹诺夫主义”与1950年代上半期的中国文坛 —— 以 《译文》 为例（1953年7月号 — 1956年3月号）= Zhdanovism and chinese literature in the first half of the 1950s —— using Yi Wen as an example (vol.7, 1953 - vol.3 1956) - 崔峰 Cui Feng (复旦大学出版社 Fudan University Press, 2019)
1950年上半期，在苏联文坛发生重大变革之时，受到苏联文坛批判的“日丹诺夫主义”却在中国文坛大行其道。本文将以当时中国大陆唯一一份公开发行的专门刊载外国文学的期刊《译文》为例，结合“日丹诺夫主义”对《译文》在文章刊载、方针调整上的影响，观察和思考如下现象和问题：为何《译文》要坚守苏联文坛开始放弃的文艺观念？它对《译文》的办刊方针产生了怎样重大的影响？为什么在“日丹诺夫主义”式的文学作品在《译文》“一统天下”的情况下，会有少量苏联的“解冻文学”被译介进来？两种文学思潮的并存又说明了怎样的问题？通过这些问题的解决，深入观察1950年代上半期,政治环境、时代发展如何影响了当时中国文坛对外国文学的介绍与翻译。 In the first half of the 1950s, great changes took place in the Soviet literature with Zhdanovism becoming the locus of criticism. As the only literary journal officially approved to publish foreign literature in Mainland China, Yi Wen, however, published a number of literary works and theoretical articles advocating Zhdanovism against the policy background of “Leaning-to-one-side (the Soviet Union).” Why did Yi Wen choose to adhere to the literary concept abandoned by the Soviet? How did the approach impact Yi Wen’s vision of itself? Why did Thaw Literature appear in Yi Wen when the journal was predominated by the literature of Zhdanovism? What can we infer from the co-existence of these two diametrically different literary trends in Yi Wen? By exploring these questions, we get an extensive in-depth look into how the political and social elements affect the translation and introduction of foreign literature in the first half of the 1950s China.